Where are rooted networks in digital political ecologies? - Hawkins, Roberta; Nelson, Ingrid L. (Frontiers in Human Dynamics, 2022)
This perspective piece contends that political-ecological relations are already digital and that feminist analyses help reveal their often-overlooked power relations. We argue that as digital political ecologies research grows in popularity, there is widespread omission and forgetting of key epistemological lessons from feminist political ecologies, such as rooted networks. Here, we remind readers of rooted networks lessons, and we distill them into suggested writing strategies for researchers. Such rooted network writing strategies may seem inefficient and may take up space and time, but as feminist political ecologists concerned with digital relations, we see them as necessary.